Aggression in mental health residential facilities: A systematic review and meta-analysis. (July 2018) - Bulgari, Viola; Ferrari, Clarissa; Pagnini, Francesco; de Girolamo, Giovanni; Iozzino, Laura
Abstract: Objectives: To estimate the prevalence of aggression exhibited by patients living in community residential facilities and to identify risk factors for such aggression. Methods: A systematic review with meta-analysis was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The protocol was registered in the International Prospective Register of Systematic Reviews (PROSPERO) dataset (registration number: CRD42016042475). PubMed, Scopus and Web of Science were searched for studies published prior to February 21st 2017. Studies reporting the number of patients who perpetrated aggressive behavior in residential facilities were included. Methodological quality, publication bias, and the role of moderators were assessed. A pooled effect size was calculated for each outcome. Factors affecting between-study heterogeneity were analyzed using sub-groups and meta-regression analysis. Results: Ten studies met the inclusion criteria, for a total sample of 3760 patients. The pooled prevalence of aggression in residential facilities was 29% (95% CI 0.17–0.42) with a high heterogeneity and variability among studies. History of violence, personality disorders, lifetime substance and alcohol misuse were found significantly associated with aggression. Conclusion: Aggression in residential care services is common. Certain individual factors are associated to an increased risk for such aggression. Highlights: A limited number of studies on aggression in residential facilities were found. Among the 3760 patients in residential facilities, 29% exhibited aggression. History of violence was the factor most associated with aggression.